Mukawwin ad-Dars al-Lugawi bi al-Mustawā aṡ-Ṡānawī al-I’dādī bi al-Magrib min Istirātījiyyah at-Tadrīs ilā Asālīb at-Taqwīm: مكون الدرس اللغوي بالمستوى الثانوي الإعدادي بالمغرب من استراتيجية التدريس إلى أساليب التقويم - Fatima Ezzahraa Elassali (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2024)
This study shows the importance of language lessons in improving linguistic skills, for the learning and the mastery of the Arabic language, namely: listening, speaking, reading, and writing. The study also clarifies the purpose of language lesson class, which is achieving several competencies for the learner to enable him/her to communicate effectively. The study shows as well some difficulties of teaching methodologies of the language lesson and its evaluation in middle schools in Morocco, through the adoption of the analytical descriptive approach in analyzing the problem under study. And through the adoption of the interpretive inference approach in stating the reasons and in revealing the challenges, which hinder the success of the teaching and the evaluation processes. The study concludes that the teaching methods of language lessons are inadequate. The time frame of its teaching is short. The way it is evaluated has several gaps. Also, the language class is irrelevant to the teaching reality and to the pedagogical condition of the teacher.